Sleepiness at the wheel across Europe: a survey of 19 countries - Goncalves, M (2015)
The European Sleep Research Society aimed to estimate the prevalence, determinants and consequences of falling asleep at the wheel. In total, 12 434 questionnaires were obtained from 19 countries using an anonymous online questionnaire that collected demographic and sleep‐related data, driving behaviour, history of drowsy driving and accidents. Associations were quantified using multivariate logistic regression. The average prevalence of falling asleep at the wheel in the previous 2 years was 17%. Among respondents who fell asleep, the median prevalence of sleep‐related accidents was 7.0% (13.2% involved hospital care and 3.6% caused fatalities). The most frequently perceived reasons for falling asleep at the wheel were poor sleep in the previous night (42.5%) and poor sleeping habits in general (34.1%). Falling asleep was more frequent in the Netherlands [odds ratio = 3.55 (95% confidence interval: 1.97; 6.39)] and Austria [2.34 (1.75; 3.13)], followed by Belgium [1.52 (1.28; 1.81)], Portugal [1.34 (1.13, 1.58)], Poland [1.22 (1.06; 1.40)] and France [1.20 (1.05; 1.38)]. Lower odds were found in Croatia [0.36 (0.21; 0.61)], Slovenia [0.62 (0.43; 0.89)] and Italy [0.65 (0.53; 0.79)]. Individual determinants of falling asleep were younger age; male gender [1.79 (1.61; 2.00)]; driving ≥20 000 km year [2.02 (1.74; 2.35)]; higher daytime sleepiness [7.49 (6.26; 8.95)] and high risk of obstructive sleep apnea syndrome [3.48 (2.78; 4.36) in men]. This Pan European survey demonstrates that drowsy driving is a major safety hazard throughout Europe. It emphasizes the importance of joint research and policy efforts to reduce the burden of sleepiness at the wheel for European drivers.